E. Explore bumi / oleh, Matt Turnerr ; penerjemah, Soni Astranto ; editor, Tessa Febriani, Dwi Kartika Wardhani - TURNER, Matt; Astranto , Soni; Febriani, Tessa; Wardhani, Dwi Kartika (2008)
96 hlm ilus 2006